“La interculturalidad en el proceso formativo en la carrera de educación básica de la Universidad Tecnica de Cotopaxi, Extension Pujili” - Chicaiza Pisaña, Edison Javier (2022)
Interculturality is defined as the healthy and harmonious coexistence each of the social groups within a given space, this requires respect for each civil, social and political rights to promote the understanding each of the people and it is considered and essential value in the educational spaces. The general aim this research was to describe Interculturality in the training process of Basic Education Career of the Technical University of Cotopaxi, Pujilí Extension during the April-August 2022 academic period. It worked under a quantitative approach, by using the deductive method, which a bibliographic-documentary, field and descriptive research was developed. It was applied he survey to 228 students, 18 teachers and two authorities from Basic Education career. The results evidence, what within the Basic Education career, there are weaknesses in the different ethnic group’s harmonious coexistence, respect and recognition them, future teacher’s preparation for interculturality construction, discrimination inclusion and prevention. Regarding the training process, it was evidenced, what interculturality is not considered as a value, nor are developed subjects, which promote it. Therefore, it is considered important, what the Basic Education career strengthen interculturality as a training process fundamental value for future teachers, especially considering that Ecuador is a multiethnic country.